Coronary artery stabilization causes endothelial damage: an electron microscopic study on dogs - (:unkn) unknown (ELSEVIER SCI LTD, 2001)
In recent years, to protect patients from adverse effects of cardiopulmonary bypass, off-pump coronary artery bypass operations are performed. In these operations, effective coronary artery immobilization is the standard for a fine anastomosis, This is usually maintained with the help of prolene immobilization sutures, bulldog occluders or mechanical epicardial devices, The aim of this study is to show whether these stabilization devices cause any damage to the coronary artery endothelium. Sixteen dogs are included in this study and are divided into four groups. The control group consisted of one dog (Group I) and different immobilization techniques are applied to the other groups, which were five dogs each (Groups II, III, and IV). Coronary artery biopsies are obtained, then the samples are studied under scanning electron microscope (SEM) for endothelial injury and all samples are scored. Among the techniques used, bulldog occluders caused less injury on the coronary endothelium than the prolene sutures. (C) 2001 The International Society for Cardiovascular Surgery. Published by Elsevier Science Ltd. All rights reserved.
Keywords: off-pump; coronary artery bypass; endothelial injury; CARDIOPULMONARY BYPASS; ATHEROSCLEROSIS; PATHOGENESIS